GEOGRAPHY TEACHERS' PERCEPTIONS OF BALURAN NATIONAL PARK AS A GEOGRAPHY LEARNING RESOURCE - Ramadhita, Novia Putri; Trisnawati, Maria; Zid, Muhammad; Hotimah, Oot (Universitas Muhammadiyah Surakarta, 2024)
It is very important for students to introduce the process of learning geography at the secondary school level to the scope of the environment and its use in everyday life as a geographical science laboratory, one of which is the Baluran National Park. The aim of this research is to identify geography teachers' perceptions of Baluran National Park as a geography learning resource. The research method used descriptive quantitative with a full sample of 16 geography teachers at SMAK BPK Penabur. The research results showed that the majority of geography teachers gave a positive assessment of the use of Baluran National Park as a learning resource. In the process of utilizing Baluran as a Geography Learning Resource, there are supporting factors including the entire potential of Baluran National Park in terms of physical, nonphysical and infrastructure. Inhibiting factors include the internal conditions of the school which include implementation time, permits, distance to the location and the educational calendar. Through research, it is recommended to utilize Baluran National Park as a Geography Learning Resource, especially for schools in East Java Province.